Myeloid-specific fatty acid transport protein 4 deficiency induces a sex-dimorphic susceptibility for nonalcoholic steatohepatitis in mice fed a high-fat, high-cholesterol diet - Göcebe, Deniz; Jansakun, Chutima; Zhang, Yuling; Staffer, Simone; Tuma-Kellner, Sabine; Altamura, Sandro; Muckenthaler, Martina; Merle, Uta; Herrmann, Thomas; Chamulitrat, Walee (American journal of physiology. Gastrointestinal and liver physiology, 2023)
Download figureDownload PowerPoint